Analisis Berpikir Kritis Matematis Siswa Kelas XI MIPA 2 SMA Negeri 1 Sindue Tombusabora Ditinjau dari Jenis Kelamin - Ruzi Rifai; Sutji Rochaminah; Paloloang Muhammad Fachri B; Pathuddin (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to describe the mathematical critical thinking skills of class XI MIPA 2 students of SMA Negeri 1 Sindue Tombusabora in terms of gender. The study used a qualitative descriptive approach with two students with high mathematical abilities, one male and one female, selected purposively. Data were collected through a mathematical critical thinking ability test on the topic of circle equations and semi-structured interviews, then analyzed using the interactive model of Miles, Huberman, and Saldaña based on the FRISCO indicators (Focus, Reason, Inference, Situation, Clarity, and Overview). The results showed that both subjects were able to fulfill all indicators of mathematical critical thinking. The differences found lay in the solution strategy, namely male students tended to use more efficient and direct steps, while female students presented more systematic and detailed solutions. However, both subjects still experienced errors in interpreting the radius in the circle equation problem and were not able to identify these errors in the final evaluation stage. These findings indicate that the mathematical critical thinking skills of high-ability students still need to be strengthened, especially in the aspects of evaluating and verifying the results of problem solving.